Market regulation and economic interdependence: Capital supply and aggregate demand in the twentieth century - Simone Selva (The European Association for Banking and Financial History (EABH), 2017)
This contribution offers a comparison between the economic crises of the late-1920s and the first energy crisis of the 1970s through an inquiry into the changing balance between the transnational supply of capital and domestic aggregate demand for fixed capital formation and consumer goods. Its aim is to offer a new interpretation of the concept of international economic interdependence. It starts by outlining the early definition of interdependence offered in the international political economy literature and within the American policymaking elites from World War II to the 1960s. Then, it provides a reappraisal of the New Economic History School's approach to the subject. Thereafter, it investigates the two historical watersheds to cast light both on the different role of Federal Reserve and the international economic institutions to manage the ratio of liquidity supply to aggregate demand, and on the importance of transnational capital flows and gold.
Keywords: N22; N12; 330; economic interdependence; financial crises; US foreign economic relations; supply side; aggregate demand; Federal Reserve; Great Slump; energy crises; Volcker revolution; cliometric revolution